Analisis Sentimen Tanggapan Masyarakat Terhadap Penutupan TikTok Shop Menggunakan Metode Naïve Bayes - Fadli, Khairul; Hasan, Firman Noor (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
E-commerce has become an important role in driving the economy, many business actors, especially MSMEs, depend on selling their products online. E-commerce continues to experience extraordinary growth, many breakthroughs have been made to improve its systems and services. One of them is social commerce which utilizes social interactions from social network users, for example TikTok Shop. However, the government changed regulations regarding social commerce which resulted in the closure of TikTok Shop operations in Indonesia, which many reactions and opinions from the public. Therefore this research was conducted with aim of analyzing public sentiment towards the closure of TikTok Shop. This research uses 1233 data taken and collected from social media X in the range September to December 2023. This research also uses the Naïve Bayes Classifier algorithm method with a training data to test data ratio of 80:20. This research resulted in accuracy of 90,24%, precision of 74,33%, and recall of 100%. The large number of negative sentiments in this sentiment analysis shows the public’s disappointment with the policy changes carried out by the government which resulted in the closure of TikTok Shop operations in Indonesia.